Design and Simulation Analysis of a New Frictionless Synchronizer - Chen Yongzhong; Zhu Bo; Zhang Nong (Jixie chuandong)
A new type of frictionless synchronizer is designed，and its three-dimensional model is built by using the software CATIA. The three-dimensional model is imported into Adams to establish a virtual prototype model and a two-gear pure electric vehicle model is built in Matlab/Simulink which is used to simulate the speed synchronization and backing process of the new synchronizer. The simulation results show that the jerk produced by the new type of synchronizer in the speed synchronization and backing process is reduced and the required time of speed synchronization and backing is also greatly reduced，which reduce the power interruption and shift frustration in the process of automobile shift，comparing with the traditional synchronizer which relies on friction to achieve speed synchronization. Finally，the influence of vehicle speed in synchronization process, helical spring stiffness and shift force for the synchronization process of frictionless synchronizer is analyzed.